Pyridine mediated transition-metal-free direct alkylation of anilines using alcohols via borrowing hydrogen conditions. Issue 88 (15th October 2020) - Pothikumar, Rajagopal; Bhat, Venugopal T; Namitharan, Kayambu
Abstract : Herein, we report aza-aromatics based organic mediators as a readily accessible alternative to the traditional approach of using transition metal catalyst systems for the activation of alcohols in borrowing hydrogen reactions. Abstract : Herein, we report pyridine and other similar azaaromatics as efficient biomimetic hydrogen shuttles for a transition-metal-free direct N-alkylation of aryl and heteroaryl amines using a variety of benzylic and straight chain alcohols. Mechanistic studies including deuterium labeling and the isolation of dihydro-intermediates of the benzannulated pyridine confirmed the role of pyridine and a borrowing hydrogen process operating in these reactions. In addition, we have extended this methodology for the development of dehydrogenative synthesis of quinolines and indoles, as well as the transfer hydrogenation of ketones.